2021
DOI: 10.3390/ijerph18062833
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Lifestyle Factors Related to Cost and Frequency of Hospitalization in European Older Adults

Abstract: Individuals’ lifestyles play an important role in healthcare costs. A large part of these costs is derived from hospitalizations. With the aim of determine the relationship between lifestyle and the likelihood of hospitalization and associate costs in older adults, this study used the Survey of Health, Aging, and Retirement in Europe. Generalized regression models for panel data were developed and adjusted hospitalization costs derived from the length of hospital stay were also estimated. The average adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Our study shows that engaging in both vigorous and moderate physical activity and having greater muscle strength are associated with a reduced risk of hospitalization. These findings are consistent with those of a previous study in European countries [10], which found that both individuals with good muscle strength and those engaging in vigorous or moderate physical activity more than once a week significantly reduced the likelihood of hospitalization. Various studies over the years have reported similar results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study shows that engaging in both vigorous and moderate physical activity and having greater muscle strength are associated with a reduced risk of hospitalization. These findings are consistent with those of a previous study in European countries [10], which found that both individuals with good muscle strength and those engaging in vigorous or moderate physical activity more than once a week significantly reduced the likelihood of hospitalization. Various studies over the years have reported similar results.…”
Section: Discussionsupporting
confidence: 92%
“…A previous work used cross-country time series data in a generalized linear model for panel data to analyze the importance of a set of determinants of access to the healthcare system [10]. However, as explained in the introduction section, a common element missing from this previous research is the ability to take into account cross-country variations in access to the health system (using doctor visits or hospitalizations).…”
Section: Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study explored which sociodemographic features may influence this phenomenon. Previous research has pointed out features that have an impact on the demand for social services [ 36 , 37 , 38 , 39 ]. Therefore, we analyzed demographic and economic data divided geographically by CSS coverage area.…”
Section: Introductionmentioning
confidence: 99%